Magnetic anomalies and rock magnetism of basalts from Reykjanes (SW-Iceland) - Dietze, Frank; Kontny, Agnes; Heyde, Ingo; Vahle, Carsten (Studia Geophysica et Geodaetica)
This study presents rock magnetic properties along with magnetic field measurements of different stratigraphic and lithologic basalt units from Reykjanes, the southwestern promontory of the Reykjanes peninsula, where the submarine Reykjanes Ridge passes over into the rift zone of southwestern Iceland. The basaltic fissure eruptions and shield lava of tholeiitic composition (less than 11500 a old) show a high natural remanent magnetization (NRM, Jr) up to 33.6 A/m and high Koenigsberger ratio (Q) up to 52.2 indicating a clear dominance of the NRM compared to the induced part of the magnetization. Pillow basalts and picritic shield lava show distinctly lower Jr values below 10 A/m. Magnetic susceptibility (κ) ranges for all lithologies from 2.5 to 26×10-3 SI. Heterogeneously distributed titanomagnetite with small grain sizes is the main carrier of magnetization. Magnetic susceptibility vs. temperature (κ-T) curves reveal multiple Curie temperatures from 35 to 570 °C suggesting different Ti-concentrations in titanomagnetite. A minor oxidation to titanomaghemite is indicated by the irreversibility of some of the κ-T curves. Intra flow variation of the magnetic minerals is relatively high depending on crystallization history and resulting primary composition and amount of titanomagnetite as well as high-temperature oxidation. The total geomagnetic field was measured for regional field variations along three profiles normal to the spreading zone at Reykjanes. These measurements along with the rock magnetic data and field observations were used for modeling the geological subsurface. The models are in agreement with a feeder dyke system related to the youngest Stampahraun 4 fissure eruption in the western part and a hydrothermally active fault system in the eastern part of Reykjanes. Furthermore, topographic features like fault scarps, pillow basalt - hyaloclastite ridges and shield lava are considered. Frank Dietze . [et. al.]. Obsahuje bibliografii a bibliografické odkazy